Pengaruh tingkat pendidikan, tingkat kemiskinan dan tingkat pengangguran terhadap ketimpangan pendapatan di Provinsi Jambi tahun 2017-2024 - Celaudia Imelia Putri; Junaidi; Heriberta (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to: 1) analyze the dynamics of education levels, poverty levels, and unemployment levels in districts/cities in Jambi Province from 2017 to 2024. 2) analyze the effect of education levels, poverty levels, and unemployment levels on income inequality in districts/cities in Jambi Province from 2017 to 2024. The analysis tool used is panel data regression. The results show: 1) income inequality fluctuates between regions, with Jambi City tending to be high (average 0.360) and Bungo relatively low (0.308). The level of education showed an upward trend, with the highest in Jambi City (78.74) and the lowest in East Tanjab (56.44). The highest poverty rate was in East Tanjab (11.34%) and the lowest in Sungai Penuh (2.96%). The highest unemployment rate is in Jambi City (8.03%) and the lowest in East Tanjab (1.73%). 2) Education level, poverty level, and unemployment level simultaneously have a significant effect on income inequality in regencies/cities in Jambi Province in 2017-2024. Partially, the level of education has a positive and significant effect, the poverty rate has a positive and significant effect, and the unemployment rate has a positive and significant effect on income inequality in districts/cities in Jambi Province from 2017 to 2024.